(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In this scientific article, the issues of improving the organizational and legal basis of investigative activities in the detection of customs crimes in the Republic of Uzbekistan today are explained. In particular, practical and legal problems in the detection of crimes in the customs field and proposals for their solution are described.